Private equity challenge - sprouts farmers market´s leveraged buyout - Ferreira, José Pedro Bilbao (2021)
This paper consists of a proposal for the leveraged buy out of Sprouts Farmers Market ,a Natural and Organic Supermarket chain that operates an et work of stores in the United States of America. A value creation strategy and business plan were outlined, after a thorough analysis of the sector, competitive land scape as well as the growth opportunities for the company. Subsequently, a valuation exercise was performed with resource to several methods to determine the appropriate entry price. Lastly, a capital structure aiming for return maximization is suggested as well as the key diligence areas.